On numerical solutions for the Caputo-Fabrizio fractional heat-like equation - Körpınar, Zeliha (Serbian Society of Heat Transfer Engineers, 2018)
In this article, Laplace homotopy analysis method in order to solve fractional heatlike equation with variable coefficients, are introduced. Laplace homotopy analysis method, founded on combination of homotopy methods and Laplace transform is used to supply a new analytical approximated solutions of the fractional partial differential equations in case of the Caputo-Fabrizio. The solutions obtained are compared with exact solutions of these equations. Reliability of the method is given with graphical consequens and series solutions. The results show that the method is a powerfull and efficient for solving the fractional heat-like equations with variable coefficients. © 2018 Society of Thermal Engineers of Serbia.
Keywords: Approximate solution; Caputo-Fabrizio derivative; Fractional heat-like equations; Laplace homotopy analysis method